Knowledge, Attitude, and Practice Towards Face-Mask Use Amid the Coronavirus 2019 Pandemic Among Public Transport Drivers in Gondar Town, A Cross-Sectional Study - Dawit Kumilachew Yimenu; Asfaw Jejaw; Ehit Haylu; Semira Kassahun; Zemene Demelash Kifle (SAGE Publishing, 2022)
Background. Coronavirus disease (COVID-19) is a highly communicable virus that continues to interrupt livelihoods, predominantly those of low-income segments of society. For the prevention of respiratory infections like the current COVID-19 outbreak, face masks are considered an effective approach. Objective. This study intended to assess the knowledge, attitude, and practice of public transport drivers towards face mask use amid the COVID-19 pandemic in Gondar, Ethiopia. Methods. A cross-sectional study was conducted among 412 public transport drivers in Gondar town from July to September 2021. The study subjects were recruited using a simple random sampling technique after proportionally allocating the sample size from the total number of public transport drivers, and finally, study subjects were selected using the convenience sampling method to select the participant drivers working in Gondar Town. The data were collected by face-to-face interview administered questioners and an on-the-spot observational checklist. Results. A total of 412 public transport drivers have participated in the study. The mean age of the respondents was 32.75 years (±8.75 years). The majority of the participants were Bajaj drivers 193 (46.84%). Among the responders, 114 (27.67%) of them use radio to gather information about the pandemic and 50 (12.14%) of them had reported being caught by COVID-19. Meanwhile, only 32 (7.77%) were vaccinated against COVID-19. Drivers that had a diploma level of education were found to be 87.7% less knowledgeable than degree holders (AOR .123, 95% CI = .026, .573). Respondents that had good knowledge about COVID-19 and face masks were found to have 1.7 times more positive attitudes than those that had poor knowledge (AOR = 1.728, 95% CI = 1.150, 2.596). drivers whose family members have ever been caught by COVID-19 were found 2 times more likely to use face masks whenever they are working/driving (AOR = 2.173, 95% CI = 1.015, 4.652) than their counterparts. Conclusion. This study revealed a very low Knowledge, attitude, and practice of face mask use among public transport drivers in Gondar town. Periodic reinforcement and training programs are needed for all public transport drivers in each level for proper understanding and adherence to COVID-19 prevention protocols and the use of face masks.